The in vitro Effect of Fibers With Different Degrees of Polymerization on Human Gut Bacteria - Chen, Miao; Fan, Bei; Liu, Shujun; Imam, Khandaker Md Sharif Uddin; Xie, Yingying; Wen, Boting; Xin, Fengjiao (Frontiers in Microbiology, 2020)
Human gut bacteria contribute significantly to human health and several studies have evaluated the effects of dietary fibers on human gut bacterial ecology. However, the relationship between different degrees of fiber polymerization and human gut bacteria is unknown. Here, we analyzed three fiber substrates with different degrees of polymerization, namely carboxymethylcellulose, β-glucans, and galactooligosaccharides. To probe the in vitro influence of the degree of polymerization of the fiber on human gut bacteria, we measured the pH, air pressure, and short-chain fatty acid content of fecal fermentation supplemented with these fiber substrates, and sequenced the 16S ribosomal RNA genes of the microbial community in the fiber-treated fermentations. The butyric acid concentration was shown to decline with decreasing degree of polymerization of the fiber. Illumina Miseq sequencing indicated that the degree of polymerization might have an influence on human gut microbial diversity and abundance. Principal coordinate analysis unveiled a relationship between the degree of fiber polymerization and the gut bacterial community. Specific microbiota operational taxonomic units (OTUs) within the genera Escherichia-Shigella, Fusobacterium, and Dorea were proportional to the degree of fiber significantly, whereas OTUs within the genera Bifidobacterium, Streptococcus, and Lactobacillus were inversely correlated with the degree of polymerization. Correlation analysis between the fiber degree of polymerization and gut bacteria may demonstrate the effect of fibers on gut microbiota, and subsequently, on human health.